THE CRIMINAL POLICY OF TRADEMARKS AND OMNIBUS LAW FOR INTELLECTUAL PROPERTY RIGHTS - Ifrani, Ifrani (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2020)
From the Global Intellectual Property Center (GIPC) survey, Indonesiastill considered weak in protecting intellectual property. Then the political direction of law began to look at the concept of the omnibus law to promote the ease of doing business (EoDB). Therefore, the purpose of this study is to analyze first, the legal protection issues of famous brand holders in Act No. 20/2016 through political instruments and criminal law policies. Secondly, the concept of the omnibus law as iusconstituendum of the Act Related to Indonesian Intellectual Property in the politicalperspective of criminal law. The normative method was chosen because of the objectof the study on the principles of law, theories, and doctrines of jurisprudence. The results of this study show that although Indonesia’s IPR index score increased in2019, it’s global ranking declined. This means that despite increases in scores, Indonesia’s IPR enforcement tends to be stagnant when compared to other countries.The IPR-related Act can be combined into an omnibus law. The aim is to simplify the laws of Patents, Trademarks, Copyrights, Industrial Designs, Layout Designsof Integrated Circuits, and Communal Investment Credit which greatly affect the economy and investment in Indonesia.